The impact of user behavior on energy consumption - a case study on Kilyos campus dormitories - Kazar, Gökhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Since the buildings consume approximately 40% of the total energy in the world, the energy e cient buildings have been gained an importance for recent years. Various approaches such as energy e cient measures and renewable energy techniques have been developed to achieve high energy performance buildings. To assess the energy performance of the buildings, di erent energy simulation tools have been developed. However, there is a gap between the actual and the estimated energy consumption, because of not accurately considering the user energy behavior in the energy simulation tools. In this study, to demonstrate the gap between real and predicted energy consumption, the energy consumers were classi ed based on their energy consumption preferences in the buildings. The survey was conducted with 529 students on Bogazici University Kilyos Campus dormitories. The students were de ned in three di erent behavior groups by using cluster analysis. Three groups were identi ed as Cluster A, B and C based on their electricity consumption attitude and time spent in the rooms. Using the cluster analysis results, 6 di erent energy analyses were performed for each dormitory building. In the rst three energy analysis, all the students in each of the dormitory were considered as belonging to just one cluster. In addition, all cluster groups were assigned to each dormitory building based on the actual distribution ratio. Besides, the default settings provided by DesignBuilder and Green Building Studio were also used to estimate energy consumption. The results show that the electricity consumption and carbon emission can be di erent in crucial levels by accounting of user energy consumption in the energy performance analysis.
Keywords: Energy consumption.